Comprehensive phytochemical profiling and in-silico evaluation of endemic medicinal plant Symplocos obtusa - Malavika, J.; Thenmozhi, K. (Sciences of Phytochemistry, 2026)
Plants rich in phytochemical compounds are a vital reservoir with great medicinal potential. Among them, Symplocos obtusa Wall. Ex G. Don., commonly known as 'blunt-leaved Symplocos', is an unexplored endemic medicinal plant species belonging to the distinguished plant family Symplocaceae. The present study undertakes a comprehensive phytochemical profiling of S. obtusa, coupled with in vitro and in-silico approaches. Screening of the ethanolic leaf extract of S. obtusa revealed several phytochemical constituents, with highest extractive yield (6.0%) and higher total phenolic (4.30±0.02mg GAE/g), tannin (2.91±0.02mg GAE/g), and flavonoid content (71.15±0.86mg RE/g). Furthermore, a thorough analysis of the phytocompounds and their therapeutic efficacy was conducted using Fourier Transform Infrared Spectroscopy (FTIR), Gas Chromatography-Mass Spectrometry (GC-MS), and other major in-silico approaches, such as toxicity prediction. Moreover, in vitro antioxidant studies were conducted to evaluate the therapeutic potential of S. obtusa. FTIR confirmed the presence of different functional groups, and GC-MS analysis identified 19 key phytochemical compounds with pharmacologically significant functions. In vitro antioxidant assays confirmed potential antioxidant activities of the plant species with an IC50 of (26.55±0.61µg/mL) in DPPH, 27.09±0.11 µmol/g (ABTS•+@), 51.38±0.08 mg/g in phosphomoleybdenum assay, and suggest its therapeutic relevance. In-silico evaluations further supported the pharmacological relevance and safety of the identified compounds. Integrative in vitro and in-silico evaluation indicated favourable drug likeness and low predicted toxicity, with most compounds belonging to toxicity classes IV-VI. These findings establish S. obtusa may serve as a promising candidate for pharmacological exploration and drug discovery, particularly in the development of plant-derived therapeutic agents.